Electrochemical studies of grid and linear type M^2+ (M=Zn, Cd and Pb) complexes of a bis-(hydrazone) bearing two symmetric carboxylic groups - Giraldo, Wilson; Romero, Elkin; Chaur, Manuel (Revista de Ciencias, 2017)
Herein we present the preparation of a bis-(hydrazone) containing a pyridine-pyrimidine-pyridine framework. This compound can be visualized as a double arm system able of coordinating two metal ions in a terpyridine-like manner. By NMR (1D and 2D) it was determined a transoid conformation and an E configuration around the two imine double bonds. Complexation with M2+ (M = Zn, Cd, and Pb) ions resulted in grid and linear type structures which were studied by cyclic and squared wave voltammetry at different temperatures. No linear correlations of the redox potentials as a function of temperature were observed. The latter is likely due to rearrangements in the structure or to spin crossover events. The present results deserve further studies on the electronic properties of these types of compounds for the development of smart materials.